Pengaruh Model Inkuiri Terhadap Hasil Belajar IPS Pada Siswa Kelas VI SDN Trawas 1 - Ahmad Saifullah; Oktaviani Adhi Suciptaningsih (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
This study aimed to investigate the effect of inquiry model on students' learning outcomes in social studies at the elementary school level. The study employed an experimental research design, using a sample of 23 sixth-grade students from SDN Trawas 1. The results showed that the use of the inquiry model in social studies significantly improved students' learning outcomes compared to the conventional method. In teaching social studies, the inquiry model can be applied by choosing topics that are interesting and relevant to students' daily lives. Thus, the use of the inquiry model in teaching social studies at the elementary school level can provide significant benefits to students, such as improving their learning outcomes and motivating them to learn independently and creatively.